2005
DOI: 10.1111/j.1365-2966.2005.08583.x
|View full text |Cite
|
Sign up to set email alerts
|

Group, field and isolated early-type galaxies - I. Observations and nuclear data

Abstract: This is the first paper of a series on the investigation of stellar population properties and galaxy evolution of an observationally homogeneous sample of early-type galaxies in groups, field and isolated galaxies.Here we present high signal-to-noise ratio (S/N) long-slit spectroscopy of 86 nearby elliptical and S0 galaxies. Eight of them are isolated, selected according to a rigorous criterion, which guarantees a genuine low-density subsample. The present survey has the advantage of covering a larger waveleng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
98
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 61 publications
18
98
1
1
Order By: Relevance
“…However, other studies show that the structural relations depend on wavelength (Jørgensen et al 1996;Hudson et al 1997;Pahre et al 1998;Scodeggio et al 1998;Jun & Im 2008). -As far as the environment is concerned, several studies imply that the structural relations and/or the structural parameters of galaxies are affected by the environment (Bender et al 1992(Bender et al , 1998Trujillo et al 2001Trujillo et al , 2002Bernardi et al 2003b;Aguerri et al 2004;Gutiérrez et al 2004;Denicoló et al 2005;Jørgensen et al 2005), although other studies reach exactly the opposite conclusion (de la Rosa et al 2001;Treu et al 2001;Evstigneeva et al 2002;Gonzáles-García & van Albada 2003;Reda et al 2004Reda et al , 2005Nigoche-Netro et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies show that the structural relations depend on wavelength (Jørgensen et al 1996;Hudson et al 1997;Pahre et al 1998;Scodeggio et al 1998;Jun & Im 2008). -As far as the environment is concerned, several studies imply that the structural relations and/or the structural parameters of galaxies are affected by the environment (Bender et al 1992(Bender et al , 1998Trujillo et al 2001Trujillo et al , 2002Bernardi et al 2003b;Aguerri et al 2004;Gutiérrez et al 2004;Denicoló et al 2005;Jørgensen et al 2005), although other studies reach exactly the opposite conclusion (de la Rosa et al 2001;Treu et al 2001;Evstigneeva et al 2002;Gonzáles-García & van Albada 2003;Reda et al 2004Reda et al , 2005Nigoche-Netro et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also discovered that the structural relations and/or the structural parameters of galaxies are affected by the environment (Bender et al 1992(Bender et al , 1998Trujillo et al 2001Trujillo et al , 2002Bernardi et al 2003b;Aguerri et al 2004;Gutiérrez et al 2004;Denicoló et al 2005;Jørgensen et al 2005), although other studies have reached exactly the opposite conclusion (de la Rosa et al 2001;Treu et al 2001;Evstigneeva et al 2002;Gonzáles-García & van Albada 2003;Reda et al 2004Reda et al , 2005Nigoche-Netro et al 2007). This second set of results suggest that galaxies very quickly absorb the changes caused by gravitational interactions, not keeping memory of these changes in regard to the structural relations.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the emission corrections derived from the [OIII]λ5007 and Hα lines, respectively, is also performed by Denicoló et al (2005a) for their sample of early-type galaxies. The authors show that the differences in the emission corrections derived through the two methods are small for the majority of galaxies, but argue that it is very dangerous to rely on the use of the [OIII]λ5007 alone because the [OIII]λ5007/Hβ ratio may be very different from galaxy to galaxy.…”
Section: Hβ Correction For Emission Infillingmentioning
confidence: 99%
“…Denicoló et al (2005a) adopt an absorption value on the basis of the Hα EW measured for their sample of stars (mainly K). Differently, as described in Papers I and II, we computed the emitted flux in the Hα line using, as a reference, the spectrum of an elliptical galaxy (NGC 1426) lacking emission lines or dust.…”
Section: Hβ Correction For Emission Infillingmentioning
confidence: 99%
“…Some papers have found that this dispersion depends on both luminosity (Bender et al 1992;Jørgensen et al 1996;Hyde & Bernardi 2009) and the environment (Bernardi et al 2003b;Denicoló et al 2005). The behaviour of the intrinsic dispersions in the FJR and the KR have not been studied thoroughly because a third variable is believed to cause most of the intrinsic dispersion in both these relations.…”
Section: Introductionmentioning
confidence: 99%